Effects of Crop Rotation and Management System on Water‐Extractable Organic Matter Concentration, Structure, and Bioavailability in a Chernozemic Agricultural Soil. Issue 1 (1st January 2013) - Xu, Na; Wilson, Henry F.; Saiers, James E.; Entz, Martin
Abstract : Water‐extractable organic matter (WEOM) in soil affects contaminant mobility and toxicity, heterotrophic production, and nutrient cycling in terrestrial and aquatic ecosystems. This study focuses on the influences of land use history and agricultural management practices on the water extractability of organic matter and nutrients from soils. Water‐extractable organic matter was extracted from soils under different crop rotations (an annual rotation of wheat–pea/bean–wheat–flax or a perennial‐based rotation of wheat–alfalfa–alfalfa–flax) and management systems (organic or conventional) and examined for its concentration, composition, and biodegradability. The results show that crop rotations including perennial legumes increased the concentration of water‐extractable organic carbon (WEOC) and water‐extractable organic nitrogen (WEON) and the biodegradability of WEOC in soil but depleted the quantity of water‐extractable organic phosphorus (WEOP) and water‐extractable reactive phosphorus. The 30‐d incubation experiments showed that bioavailable WEOC varied from 12.5% in annual systems to 22% for perennial systems. The value of bioavailable WEOC was found to positively correlate with WEON concentrations and to negatively correlate with C:N ratio and the specific ultraviolet absorbance of WEOM. No significant treatment effect was present with the conventional and organic management practices, which suggested that WEOM, as the relatively labile pool in soil organic matter, is more responsive to the change in crop rotation than to mineral fertilizer application. Our results indicated that agricultural landscapes with contrasting crop rotations are likely to differentially affect rates of microbial cycling of organic matter leached to soil waters.